THE RIGHTS OF AUTISTS IN BRAZILIAN LEGISLATION: A HISTORICAL REFLECTION - Juliane Barros Generoso, Cibele; Cristiane Barros Moreira, Érica (Revista Gênero e Interdisciplinaridade, 2023)
The Federal Constitution of Brazil ensures, since 1988, that every citizen has a public, free, secular and quality education, regardless of their social, financial or physical conditions. The Declaration of Human Rights (1945) provides that every citizen has the right to live a life of freedom, justice, equality and equity. In this sense, laws are important instruments that ensure that such rights are enforced. In this way, we define as the general objective of this article to understand in the legislation what are the rights that autistic people have and what is assured to them. Through the specific objectives we will conceptualize the term “autism”, we will dialogue about the characteristics of these subjects and we will reflect on their inclusion in the educational space. The research was developed based on qualitative methodology, literature review and legislation study. It is argued that the theme is relevant, since the citizen’s quality of life and the realization of their rights must be a struggle for the whole of society in general. We believe that debate, research and reflection constitute valuable means for building an inclusive, fair and democratic society.